Existence and Quality of Data on Control Programs for EU Non-regulated Cattle Diseases: Consequences for Estimation and Comparison of the Probability of Freedom From Infection - Rapaliute, Egle; van Roon, Annika; van Schaik, Gerdien; Santman-Berends, Inge; Koleci, Xhelil; Mincu, Madalina; Gethmann, Jörn; Conrady, Beate; Knific, Tanja; Hodnik, Jaka Jakob; Berezowski, John; Carmo, Luís Pedro; et al. (Frontiers in Veterinary Science, 2021)
Some European countries have successfully implemented country specific control programs (CPs) for infectious cattle diseases that are not regulated or are regulated only to a limited extent at the European Union (EU) level. Examples of such diseases include bovine viral diarrhea (BVD), infectious bovine rhinotracheitis (IBR) and Johne’s disease (JD). The CPs vary between countries in the design and quality of collected data as well as methods used to detect disease and estimate prevalence or probability of disease freedom. Differences in disease status between countries and non-standardized approaches to assess freedom from disease pose a risk for countries with CPs for non-regulated diseases, as infected animals may influence the progress of the disease control or eradication program. The implementation of output-based standards allows estimation and comparison of the probability of freedom for non-regulated cattle diseases in European countries. The aim of the current study was to assess the existence and quality of data that could be used for estimating freedom from disease in European countries. The online data collection tool was sent to 32 countries participating in the SOUND control COST Action and was completed by 24 countries. Data on cattle demographics and data from CPs of IBR and BVD, exist in more than 50% of the response countries. However, data describing risk factors and CP of JD was reported as existing in less than 25% of the countries. The overall quality of data in the sections on demographics and CPs of IBR and BVD were evaluated as “good”, but risk factors and JD data were mostly evaluated as “fair”. Data quality was considered less good mainly due to two quality criteria - accessibility and accuracy. The results of this study showed that the quantity and quality of data about cattle populations and CPs are relatively similar in many surveyed countries. The outcome of this work provides an overview of the current situation in the European countries regarding data on EU non-regulated cattle diseases and will further assist in the development and implementation of output-based standards.